Achieving superior thermoelectric transport in bismuth antimony telluride thin films via orientation and microstructure regulation - Qu Youyang; Zhao Bing; Zhao Weiyun; Deng Yuan (National Science Open)
The electron-phonon transport properties of bismuth telluride-based thermoelectric materials are significantly influenced by crystallographic orientation and microstructure engineering. Thin-film materials are proper candidates for the study of structure-property relationship due to abundant microstructures. However, comprehensive studies on thin-film thermoelectric materials remain insufficient. Here, we synthesize p-type Bi0.5Sb1.5Te3 thin films via magnetron sputtering and followed by heat treatment. Preferential growth orientation of thin films exhibits a strong dependence on deposition conditions, allowing targeted orientation engineering through process parameter optimization. A high sputtering pressure of 3 Pa produces Bi0.5Sb1.5Te3 thin films with preferred in-plane orientation. The post-heat treatment enables precise regulation of electron-phonon coupling efficiency by engineering defect configurations. The dislocation density was reduced after annealing, and anti-site defects can also be tuned to optimized carrier concentration and mobility. After the heat annealing process under 400°C, a super high zT value of 1.49 was achieved at 313 K in Bi0.5Sb1.5Te3 thin film.